PROKRASTINASI AKADEMIK PESERTA DIDIK DI SMA NEGERI 1 GUNUNG TULEH KABUPATEN PASAMAN BARAT - Wira Solina; Ahmad Zaini (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
This resear chis motivated by thep henomenon of their students perform academic procrastinationin SMAN 1 Gunung Tuleh West Pasaman. Theresear chobjec tivetodescribe: 1).Academic procrastination learnersview sofpost ponement ofacademic assignments, 2).Judging from theinaction anddelaysina cademic tasks,3).Judging from thediscrepancy between theplanwit hactual performance,4). Judging fromdoingo theractiviti esmore enjoyable.Thisresear chis quantitative descriptive. The study population wasthe whole class XI numbered 170 people. Sampling Stratified Random Sampling technique was used with the number of 117 people. Instrumentused questionnaire. Data were analy zedusing interval. Theresult showed that: 1). Academic procrastination learners view sofpostponement ofacademic task sthat arein thelowcategory, 2). Judging from the inaction and delaysina cademic tasks thatarein the category is quite high, 3). Viewed from amismat chbetweent heplan with actualper form anceisat the low category ,4). Judging from doingo ther activities aremoref untobeona fairly high category.